2017
DOI: 10.4025/actasciagron.v39i4.32847
|View full text |Cite
|
Sign up to set email alerts
|

<b>Genetic dissimilarity among sweet potato genotypes using morphological and molecular descriptors

Abstract: ABSTRACT. This study aimed to evaluate the genetic dissimilarity among sweet potato genotypes using morphological and molecular descriptors. The experiment was conducted in the Olericulture Sector at Federal University of Jequitinhonha and Mucuri Valleys (UFVJM) and evaluated 60 sweet potato genotypes. For morphological characterization, 24 descriptors were used. For molecular characterization, 11 microsatellite primers specific for sweet potatoes were used, obtaining 210 polymorphic bands. Morphological and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…The assigning of group membership in DAPC is in agreement with the hierarchical cluster analysis; this finding is consistent with reports from other studies [ 36 , 57 , 58 ]. The high cophenetic correlation coefficient (>0.70) observed for the hierarchical cluster analysis indicates the reliability of this approach to summarize the information of dissimilarity matrices [ 34 ]. Moderate levels of admixture were observed among the inbred lines used in this study, this indicate shared ancestry among the inbred lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assigning of group membership in DAPC is in agreement with the hierarchical cluster analysis; this finding is consistent with reports from other studies [ 36 , 57 , 58 ]. The high cophenetic correlation coefficient (>0.70) observed for the hierarchical cluster analysis indicates the reliability of this approach to summarize the information of dissimilarity matrices [ 34 ]. Moderate levels of admixture were observed among the inbred lines used in this study, this indicate shared ancestry among the inbred lines.…”
Section: Discussionmentioning
confidence: 99%
“…They have been widely used in plants to evaluate genetic diversity, construct linkage maps, and association analysis [ 31 , 32 ]. However, studies have shown that joint analysis of molecular and morphological data provides in-depth insight into population structure and genetic diversity, and this has been used in different crops [ 33 , 34 , 35 , 36 , 37 ]. Belalia et al [ 38 ] demonstrated the usefulness of this method in maize by assessing the genetic diversity of 56 populations using 14 agro-morphological traits and 18 simple sequence repeat (SSR) markers.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic improvement is one of the main tools to increase crop yield in a sustainable way [1]. However, for genotype selection in breeding programs, knowledge of genetic dissimilarity among the genotypes of the population to be improved is essential [2,3]. Several molecular techniques have been used for genetic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the genetic variation in breeding population facilitates identification of useful genetic divergence imperative for cassava population improvement. Genetic divergence in breeding population is evaluated by genetic markers (Andrade et al 2017). Genetic markers such as agro-morphological markers had been used frequently in preliminary studies because they are fast and easy approach for assessing the extent of diversity among germplasm (Asare et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Elias et al (2001) also reported that morphological traits have a heritable genetic variation. As knowledge in scientific research progressed, molecular markers were noted to unravel the genetic constitution and significance of traits through DNA fingerprinting, gene link detection, identification of genotypes, gene introgression, germplasm characterization, phylogenetic analysis, and indirect selection of agronomic traits (Souza 2015;Andrade et al 2017). Such knowledge underpins the use of appropriate and reliable agro-morphological descriptor and molecular markers for the evaluation of genetic diversity (Fukuda and Guevara 1998).…”
Section: Introductionmentioning
confidence: 99%